Characterization of technological level, age of puberty and first service of Romosinuano females in Mexico - Severino Lendechy, Víctor Hugo; Perezgrovas Garza, Raúl Andrés; Muñoz González, Juan Carlos; Piñeiro Vázquez, Ángel Trinidad; Chay Canul, Alfonso Juventino (Acta Universitaria, 2019)
The aim of this study was to characterize the technological level (TL), age and weight at puberty and first service in Romosinuano (RO) heifers in Mexico. Ten production units (PU) were used. The PU have 30.0%, 40.0%, and 30.0% of low, medium, and high TL, respectively. Age (months) and weight at puberty (kg), according to the TL of the PU, were 22.0 ± 2.0 and 305.4 ± 15.3 for low TL, 20.2 ± 1.0 and 326.3 ± 10.0 for medium TL and 18.0 ± 1.6 and 340.2 ± 17.5 for high TL, respectively. The age (months) and weight at first service (kg) according to the TL of the PU were 25.0 ± 2.0 and 336.0 ± 15.3 for low TL, 23.6 ± 2.0 and 359.5 ± 12.6 for medium TL and 20.5 ± 1.5 and 366.0 ± 10.1 for high TL, respectively. The age and weight at puberty and at first service varies according to the technological level of the PU.